A Brief Review of Metallothermic Reduction Reactions for Materials Preparation. Issue 12 (7th August 2018) - Xing, Zhenyu; Lu, Jun; Ji, Xiulei
Abstract: Metallothermic reduction reactions (MRRs) are displacement reactions that use reactive metals to reduce compounds so that metals, alloys, nonmetal elementary substances, and composites are produced, often in a scalable manner. In recent years, nonmetal materials, mainly silicon and carbon, particularly in their nanostructured forms obtained using an MRR with magnesium as the reductant, have started to attract much attention. However, reactions using other metals as the reductant have not been widely investigated yet. Furthermore, the reaction mechanisms and their controlling factors remain unclear, and much more effort is needed to advance this emerging field. Here, MRR preparation methods for metals, alloys, nanoporous silicon, nanoporous carbon, and composites are discussed as an introduction for new researchers in this field. Abstract : The production of specialty metals, alloys, nanostructured carbon, porous silicon, and nanocomposites by reducing compounds with reactive metals in metallothermic reactions is systematically summarized. Perspectives on the future development of this preparation methodology for syntheses of advanced materials are also provided.